CLINICAL DISCUSSION OF A PATIENT WITH RECURRENT VENOUS THROMBOEMBOLIC COMPLICATIONS - A. L. KOMAROV (Атеротромбоз, 2017)
The article presents a clinical discussion of the patient with recurrent venous thromboembolic complications. It also provides recommendations on modern principles of diagnostics, choice of medical tactics in patients with this pathology. Much attention is paid to the issues of anticoagulant treatment, which inadequacy or failure results in the development of severe, difficultly treatable complications.